Use of starter cultures for table olives fermentation as possibility to improve the quality of thermally stabilized olive-based paste. (April 2018) - Cosmai, Lucrezia; Campanella, Daniela; De Angelis, Maria; Summo, Carmine; Paradiso, Vito M.; Pasqualone, Antonella; Caponio, Francesco
Abstract: The objective of this work was to improve the quality of thermally stabilized olive-based paste (ObP), obtained from table olives fermented with different starter cultures. Four different trials were performed: conventional fermentation by indigenous bacteria and yeasts (Treatment 1); fermentation using commercial Lactobacillus plantarum as starter (Treatment 2); fermentation using commercial L. plantarum and selected autochthonous yeast Wickerhamomyces anomalus DiSSPA73 (Treatment 3); fermentation using commercial L. plantarum, W. anomalus DiSSPA73, L. plantarum DiSSPA1A7, and Lactobacillus pentosus DiSSPA7 (Treatment 4) on which microbiological, physicochemical, and sensory analyses were carried out. The results showed no significant influence of starter cultures on colorimetric indices. From the olives fermented using yeasts, both with and without association of selected lactic bacteria, we obtained an olive-based paste richer in phenol compounds, carotenoids, and free amino acids, which had a better volatile and sensory profile, characterized by lower amounts of the volatile compounds associable to sensory defects. Highlights: Olive-based pastes were obtained by table olives fermented with starter cultures. Treatment 3 had higher and lower organic acids and consistency values, respectively. Treatments 3 and 4 had higher content of phenol compounds, carotenoids and FAA. Treatments 3 and 4 presented a better volatile and sensory profile.